A5.15 How Micrornas Control Plasma Cells. (25th February 2013) - Schmid, Julia; Porstner, Martina; Brandl, Andreas; Roth, Edith; Winkler, Thomas; Bösl, Michael; Radbruch, Andreas; Wittmann, Jürgen; Jäck, Hans-Martin
Abstract : Background and Objectives: Our long-term goal is to understand how one class of interfering non-coding RNAs, the so-called micro-RNAs (miRNAs), regulates and fine-tunes the differentiation of mature B cells into effector cells, i.e., memory B cells and antibody-secreting plasma cells. miRNAs control the expression of specific target genes at the post-transcriptional level by binding to target sequences e.g., in the 3'-untranslated region of mRNAs, which, depending on the degree of the binding, results either in a block of translation or an accelerated degradation of the respective target mRNA. Lineage-specific deletion of the miRNA-processing DICER protein as well as of individual miRNAs revealed the importance of miRNA pathway in early steps of central B cell maturation. However, the mechanisms by which miRNA-dependent circuits control the antigen-induced phase of B cell activation of mature naive B cells and their subsequent differentiation into effector cells remain largely elusive. Methods: To change this situation we established a transgenic knock-in mouse line with a floxed allele of DGCR8, an essential subunit of the nuclear miRNA processing complex. B cell-specific deletion of DGCR8 resulted in a complete maturation block at the pro-B stage, indicating that miRNA processing is essential for central B cell maturation. We have also established a culture system that allows us to delete a floxed DGCR8 gene in freshly isolated B cells using retrovirally transduced Cre. Using this system, we found that the miRNA pathway is required for mitogen-induced in vitro proliferation of mature B cells. Results: We have also obtained genome-wide miRNA expression profiles of all major mouse B cell subsets, including long-lived plasma cells, and found a profound upregulation of one miRNA in plasma cells. Ectopic expression of this plasma cell signature-miRNA in primary mouse B cells accelerated the differentiation into antibody-secreting plasmablast, as indicated by upregulation of CD138 and enhanced IgM secretion. We also verified several targets of this miRNA, e.g., Bach2 and MiTF, that are part of the transcriptional circuit that controls germinal centre reactions and plasma cell differentiation. Conclusions: These studies will provide new molecular insights into regulatory circuits that control the production of antibodies and could potentially lead to new avenues for diagnosing or treating diseases associated with aberrant plasma cell development, e.g., primary antibody deficiencies, plasma cell malignancies, and autoimmune disorders.